Extrathymic signals regulate the onset of T cell repertoire selection. - Fairchild, P; Waldmann, H (2000)
The thymus is the principal site of T cell development, coordinating positive and negative selection of an immunocompetent repertoire. The ability of fetal thymi from C57BL/6 mice to support these selection events in culture is, however, critically dependent on the timing of their excision: whereas thymi from 16 day embryos generate mature CD4+8(-) and CD4(-)8+ thymocytes, 14 day thymi show a profound blockage in positive selection at the CD4+8+ stage. Here we show that this blockage is not due to intrinsic deficiencies in the ability of thymocytes to transduce positive selection signals, suggesting the defect to lie within the thymic microenvironment. Since vascularization of the thymus occurs at day 15 of gestation, we investigated whether the exclusion of plasma proteins from 14 day thymi was responsible. Accordingly, the addition of serum from 16 day embryos to organ cultures of 14 day thymi rescued mature CD4+8(-) and CD4(-)8+ subsets. Activity was found to reside in a low molecular weight fraction of serum, sensitive to proteolysis, which was present only transiently during ontogeny. Our data suggest that repertoire selection is initiated following "priming" of the thymic microenvironment by plasma proteins, thereby ensuring the onset of positive selection to be delayed until the entry of extrathymic proteins to which self tolerance must be established.